The leading edge : CEOs who turned their companies around; what they did and how they did it - Potts, Mark; Behr, Peter (New Delhi : Tata McGraw-Hill Publishing, 1987)
This book shows how the CEOs epitomize the new style of management for the 1980's at large corporations.
Includes index
ucj 16/01/2019
Loans
Keywords: Organizational change; Success in business